PERANAN PENGENDALIAN INTERNAL DAN STANDAR OPERASIONAL PROSEDUR PENGELOLAAN PERSEDIAAN BERAS DALAM MENUNJANG EFEKTIVITAS PENGELOLAAN PERSEDIAAN BERAS SEBAGAI BARANG DAGANGAN PADA PERUM BULOG SUB DIVISI REGIONAL III LOMBOK TIMUR - Muhammad Faishal (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
This study aims to examine the role of internal controls and standard operating procedures rice stock management in supporting the effectiveness of management of the supply of rice as merchandise at Perum Bulog sub-regional divisions III East Lombok. research sites in eastern Lombok by taking a sample of three warehouses located in the eastern Lombok warehousing complex Sakra, MasbagIk and Sukamulia. This type of research used in this research is descriptive qualitative research. Ie, by describing each event, information, and data obtained relating to the management of the supply of rice in Bulog warehouse complex sub-regional divisions III Lombok east to decipher the information, and the data in the form of qualitative narrative. The results of this study indicate there are still some weaknesses in internal control on all three of the warehouse complex. Research findings indicate several things: first incomplete personnel at each warehouse where there are warehouses that do not have officers complete as set in operational standards Bulog, both still weak supervision of the warehouse by a related party as Subdivre region Lombok East. Furthermore, the findings also show that there is not the presence of the separation of functions and duties related to the four basic tasks that Bulog warehouse receipt, storage, treatment and distribution